A relação entre o espaço escolar e violência infanto-juvenil no contexto de ação do Programa da Patrulha Escolar em Ponta Grossa - Pr - Iaroczinski, Adriane (2009)
The objective of this research is to understand the relationship between the school space and infanto-youthful violence in the context of the action the Patrol School Program in Ponta Grossa-PR. The infanto-youthful violence is heterogeneous with the constituent elements of the spatial differential to be explored. Thus, under this concept has been the objective of understanding the school and its relationship with the children and youth violence from the implementation of the Program of Patrol School in Ponta Grossa-PR. The seizure of the organization as a social space has been made by a long road of research among geographers. In this context, the approaches had the privilege structuralism between social classes and the logic of capital accumulation based in marxist theory. Despite the progress of the ideas advocated by the current thinking of some elements such as geographic categories children and adolescents do not always existed, historically have been built in their social realities. The infanto-youthful violence ancora a process that includes cultural diversity and the socioeconomic conditions, which contribute in the production of space. The geographic space produced by socially marginalized people, who are out of a pattern followed by a cultural society, are neglected and absent as actors that promote the reproduction of social space. These elements become important to consider so severe a scientific study. And it is in this perspective that the proposed research emphasizes the social segment for children and youth, as social actors processors through the dynamics of the area of school violence. It is therefore of great importance to research on infanto-youthful violence, as it refers to a discussion on the role of schools in society and the role of the State as regulator of social relations in the school, which are parts of the dynamic socio-spatial organization and also as a source of social consciousness. Using the quantitative and qualitative research sought to data collection, the field observations and interviews with actors exploratory purposes with social research through their ideas and perceptions about the school violence. These methods employed led to a result that allowed comprehensive guide the object of study of this research to better understand this phenomenon. With the quantitative results indicated the schools with the biggest indices of violence registered by the Patrol School Program that enabled the construction of the profile of the violent acts committed and suffered by infanto-youthful the social group and with the qualitative results made possible to diagnosis and to understand the expressiveness of the pertaining to school violence, from the vision of the responsible social agents in this process, educators, policemen and pupils, characterizing its evaluations and its action implemented ahead of the problematic one of the pertaining to school violence.